An Analysis of a Finnish 5th Grade German Class’s Use of an Open-Source CALL tool for Vocabulary Learning : A Case Study - Suominen, Markus (My University, 2023)
The field of computer assisted language learning (CALL) studies the usage of computers in language learning. The field got its start, many decades ago, through the creation of a few projects, such as PLATO, in which the computer was used as an educational system/program. Thanks to the advancement of different types of computer technology people have access to a wide variety of different advanced language learning tools, for example Kahoot! and Duolingo. Many of these tools are available online through a web browser. However, using a computer tool via the internet is only a method among many. For example, software can be created for mobile phones and computers in many different forms and for different use purposes. One of these purposes is language learning. Additionally, programs can be created to help with smaller sub-tasks, such as vocabulary learning. In this case study, I analysed how a multimodal CALL program was received by a small, Finnish, 5th grade class studying German. Unlike, say, Duolingo, this CALL program was not used via the Internet. It was programmed using open-source, in other words free, software and was available for use on a single personal computer, in the classroom. The program was only available on a single computer, due to administrative restrictions related to the school’s other computers. The CALL program provided the students with additional modes of meaning to benefit their language learning process. By using the program students were able to view German language words in text form. On top of this, they were also able to hear the word spoken out loud by the program and they were supplied with a visual depiction of the word, in the form of a 2D picture. The possible benefit of this multimodal output would be the added context provided by the multiple modes. This way students would encounter a single word in three different ways, at once. Students interacted with the program, by using a touchscreen. During the study, the participating students took part in two vocabulary tests, for which they were able to study using the CALL program. Data on their performance in these two vocabulary tests was gathered. Data was also gathered on their pre- and post-study vocabulary test performance. Additionally, data was gathered from the students and the teacher of the classroom, via feedback forms. The results of this study show that the students were open to the use of the CALL program and that, according to the teacher, the students were motivated by the introduction of the program. The feedback showed that many of the students would be willing to use computer technology in language learning, rather than traditional textbooks. However, due to the small number of available participants, it was impossible to draw any wider statistical conclusions based on students’ vocabulary test scores or their multimodality preferences. Nevertheless, despite the program’s limitations, from a contemporary technological standpoint, the language learning classroom was able to benefit from its use of an open-source language learning tool.
Keywords: CALL, computer tool, human-computer-interaction, multimodality, vocabulary learning